Synthesis and structure-activity relationship of L-methionine-coupled 1,3,4-thiadiazole derivatives with activity against influenza virus - TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY; KULABAŞ, NECLA (WILEY, 2022)
In previous investigations, we identified a class of 1,3,4-thiadiazole derivatives with antiviral activity. N-{3-(Methylsulfanyl)-1-[5-(phenylamino)-1,3,4-thiadiazole-2-yl]propyl}benzamide emerged as a relevant lead compound for designing novel influenza A virus inhibitors. In the present study, we elaborated on this initial lead by performing chemical synthesis and antiviral evaluation of a series of structural analogues. During this research, thirteen novel 1,3,4-thiadiazole derivatives were synthesized by the cyclization of the corresponding thiosemicarbazides as synthetic precursors. The structures and the purities of the synthesized compounds were confirmed through chromatographic and spectral data. Four L-methionine-based 1,3,4-thiadiazole derivatives displayed activity against influenza A virus, the two best compounds being 24 carrying a 5-(4-chlorophenylamino)-1,3,4-thiadiazole moiety and 30 possessing a 5-(benzoylamino)-1,3,4-thiadiazole structure [antiviral EC50 against influenza A/H3N2 virus: 4.8 and 7.4 mu M, respectively]. The 1,3,4-thiadiazole derivatives were inactive against influenza B virus and a wide panel of unrelated DNA and RNA viruses. Compound 24 represents a new class of selective influenza A virus inhibitors acting during the virus entry process, as evidenced by our findings in a time-of-addition assay. Molecular descriptors and in silico prediction of ADMET properties of the active compounds were calculated. According to in silico ADMET and drug similarity studies, active compounds have been estimated to be good candidates for oral administration with no apparent toxicity considerations.
Keywords: 1; 3; 4-thiadiazoles; ADMET; antiviral activity; influenza virus; L-methionine; virus entry; DRUG DISCOVERY; NONNUCLEOSIDE INHIBITORS; SCREENING LIBRARIES; ANTITUBERCULOSIS; REPLICATION; STRATEGIES; PREDICTION; DESIGN; HIV; 4-THIAZOLIDINONES